Craft production of albumin products from local dairy raw materials - Soloviov, Nikita; Tymchuk, Alla; Grek, Olena (My University, 2023)
Analyzing the current market for protein products, we can conclude that there has been a noticeable increase in the craft production of albumin products with various fillers, which indicates the relevance of this area for saving local dairy raw materials, as well as expanding the range, improving quality, increasing nutritional and biological value, and extending the shelf life of finished products. Аналізуючи сучасний ринок виробництва білкових продуктів, можна зробити висновок про помітне зростання крафтового виробництва альбумінних виробів з різними наповнювачами, що свідчить про актуальність цього напрямку для економії локальної молочної сировини, а також розширенню асортименту, поліпшенню якості, підвищенню харчової й біологічної цінності, подовженню термінів зберігання готових продуктів.
Keywords: альбумінні продукти; albumin products; молочна сировина; dairy raw materials; молоко; milk; кафедра технології молока і молочних продуктів